Our experience of nursing/allied health practitioner led geriatric screening and assessment of older patients with cancer – a highly accessible model of care. Issue 8 (November 2021) - Thaker, Darshit Arunbhai; McGuire, Peter; Bryant, Geoffrey; Wyld, David; Leach, Justine; Wheatley, Hermione; Snape-Jenkinson, Stella; Kelly, Bernadette; Bourke, Anne; Kennedy, Glen
Abstract: Objective: Comprehensive Geriatric Assessment (CGA) has been proven to assist development of tailored treatment plans for older patients with cancer by identifying health issues affecting their ability to complete systemic therapy or cope with and recover from cancer treatment. Materials and Methods: Metro North Hospital and Health Service (MNHHS) has significant older population with cancer. Geriatric Oncology services were commenced in February 2018 at two facilities of MNHHS [North Lakes Cancer Care Services/Caboolture Hospital (NLCCS/CBH) Cancer services and Redcliffe Hospital (RH) Cancer services]. The Geriatric 8 (G8) screening tool was administered to predict patient vulnerability and need for CGA. A bespoke CGA suite comprising of 16 assessments was used. A clinical nurse or Allied Health (AH) practitioner conducted screening, followed by CGA. Proposed care was discussed at multidisciplinary case conference and AH interventions were provided. Results: From February'2018 to July'2019, the G8 was administered to 1380 patients between the two facilities (918 patients at NLCCS/CBH and 462 patients at RH), comprising oncology and haematology patients. 825 patients (59%) showed impairment on G8 and were recommended for CGA. Another 50 patients were referred for CGA as per clinical assessment despite normal G8. 65% (572) of recommended CGAs were conducted. The most common impairments identified on CGA leading to AH referrals were timed up & go >13 s, malnutrition, polypharmacy and low mood & depression. Conclusion: The nursing/AH practitioner led Geriatric Oncology service is feasible, applicable and beneficial to patients. Further study is planned to assess the impact of the service on patients' health related quality of life and chemotherapy completion rates.